Factors Influencing the Decision to Choose International Express Parcel and Document Delivery Service Providers in Bangkok - Saisanit, Suphawadee; Nimtrakool, Kanyarat (Journal of Applied Economics and Management Strategy, 2025)
This research aimed to 1) investigate the factors influencing the decision to use international express parcel and document delivery services, and 2) compare these factors among different user groups. The study employed a quantitative approach, with data collected from a sample of Bangkok residents who have used international shipping services, selected through purposive sampling. The research instrument was a questionnaire, with content validity indices (IOC) ranging from 0.66 to 1.00 and a reliability coefficient (Cronbach’s Alpha) of 0.75. Data analysis was conducted using descriptive statistics, including frequency distribution, mean, percentage, standard deviation, and one-way ANOVA at a significance level of 0.05. The results revealed that the most influential factor in the decision to use these services was the reliability of delivery ( X ̅ = 4.43, S.D. = 0.69) followed by the organizational characteristics of the logistics service provider ( X ̅ = 4.16, S.D. = 0.76) and the service process ( X ̅ = 4.14, S.D. = 0.80). Additionally, hypothesis testing indicated that demographic factors such as education level and monthly income, as well as behavioral factors and reasons for choosing the service, significantly influenced the decision to use international shipping services at 0.05. Among these factors, the price of services had the highest Pearson correlation coefficient of 0.804, suggesting that price was the most strongly correlated with the decision to use the service, followed by service attentiveness of 0.791 and impression creation of 0.789. All these factors exhibited moderate correlations in the same direction. The findings enhance the understanding of user behavior and service needs in the context of international parcel delivery in Bangkok. These insights are valuable for logistics service providers in improving service quality and strategic development, and also serve as important input for public policy formulation by governmental agencies in the future.